Measuring Adherence in Hypertensive Patients—Pilot Study with Self-Efficacy for Appropriate Medication Use Scale in Bulgaria - Zornitsa Mitkova; Elena Dimitrova; Velislava Kazakova; Nikolay Gerasimov; Diyan Gospodinov; Javor Mitkov; Stamen Pishev; Guenka Petrova (Medicina)
Background and Objectives: Hypertension is found as the leading cardiovascular disease in Bulgaria and the most frequent lifelong condition with a high risk of non-adherence. The aim of this study is to assess the hypertension patients’ adherence to medication therapy in Bulgaria by using the self-efficacy for appropriate medication use scale (SEAMS). Materials and Methods: A cross-sectional study was conducted in the major cardiology settings in the capital Sofia and in Burgas, the fourth largest city in Bulgaria. Data were collected from January 2024 to July 2024. The SEAMS was validated in Bulgarian in a sample of patients with hypertension that made it extremely suitable for our study. We applied 19 questions. Additionally, we used Cronbach’s α, ANOVA analysis, Pearson correlation, and covariance tests for statistical significance. Results: A total of 232 patients completed the study. Both genders are almost equally distributed (49.6% male and 50.4% female). The results reveal that the increase in the number of diseases and prescribed medicinal products leads to a worsening adherence level. Advancing age negatively affects the adherence scores. The study showed that in half of the age groups studied (patients’ age: 40–49, 60–69, and 70–79), adherence in patients treated with FDCs was better or almost the same (patients’ age: 50–59) as those treated with several mono-products. Conclusions: Measuring adherence with SEAMS in the hypertensive Bulgarian population in two regions reveals a good level of adherence. Factors negatively affecting adherence were older age, polypharmacy, co-morbidity, and therapy with monoproducts.